2004
DOI: 10.2337/diabetes.53.4.1068
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome, Circulating Oxidized LDL, and Risk of Myocardial Infarction in Well-Functioning Elderly People in the Health, Aging, and Body Composition Cohort

Abstract: The object of this study was to establish the association between the metabolic syndrome and oxidized LDL (oxLDL) and to determine the risk for coronary heart disease (CHD) in relation to the metabolic syndrome and levels of oxLDL. OxLDL was measured in plasma from 3,033 elderly participants in the Health, Aging, and Body Composition study. The metabolic syndrome was defined according to criteria established in the Third Report of the National Cholesterol Education Program Expert Panel on Detection, Evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
180
2
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 290 publications
(202 citation statements)
references
References 45 publications
14
180
2
6
Order By: Relevance
“…The decrease of ox-LDL by stevioside is particularly important in view of our recent observation that ox-LDL is associated with the metabolic syndrome components obesity, hyperglycemia and insulin resistance, and hyperlipidemia in the general population. 7,8 The decrease in ox-LDL was not due to an increase in PON1 in stevioside-treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of ox-LDL by stevioside is particularly important in view of our recent observation that ox-LDL is associated with the metabolic syndrome components obesity, hyperglycemia and insulin resistance, and hyperlipidemia in the general population. 7,8 The decrease in ox-LDL was not due to an increase in PON1 in stevioside-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Moreover, we showed that ox-LDL was associated with the incidence of the metabolic syndrome 6 and with several metabolic syndrome components, especially visceral obesity. 7,8 Stevioside was found to exert antihyperglycemic and insulinotropic effects in a non-obese animal model of type 2 diabetes 9 by acting directly on pancreatic cells. 10 However, its effects on adipose tissue and obesity-associated insulin resistance, inflammation, oxidative stress and atherosclerosis have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Because a fairly strong correlation between oxidized LDL and LDL cholesterol is a consistent finding in several studies (16,17), we expressed oxidized LDL as a ratio per LDL cholesterol (oxidized LDL-to-LDL cholesterol ratio), as proposed by Holvoet et al (18).…”
Section: Laboratory Analysismentioning
confidence: 99%
“…Indeed, we have recently shown that the metabolic syndrome in humans is associated with elevated circulating ox-LDL, which predicts the risk for future myocardial infarction. 44 Inflammation plays an important role in atherosclerosis. 45 Adipocytes also contribute to these processes.…”
Section: Oxidative Stress Inflammation and Reduced Atherosclerosismentioning
confidence: 99%